2015
DOI: 10.1063/1.4932529
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for enhancement of vortex matching field above 5 T and oxygen-deficient annuli around barium-niobate nanorods

Abstract: We report the dependence of critical temperature (Tc), the irreversibility line, the microstructure of nanorods with perovskite-based barium niobates (BNOs), and the c-axis length of the YBa2Cu3Oy (Y123) superconducting matrix on the BNO-doping level and growth temperature for Y123 thin films with BNO nanorods. The characteristic field (Bcr) determined from the vortex-Bose-glass-like irreversibility lines in Y123+BNO films is strongly correlated to the BNO nanorod density and the growth temperature. Despite a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Awaji et al reported that wellaligned nanorods play an important role in achieving the high performance of the B irr . 13) Horii et al reported that B irr at T=T c = 0.9 increased with B ϕ up to ∼5 T and became saturated (or decreased) for B ϕ > 5 T. 14) Therefore, we expect that the introduction of well-aligned nanorods with B ϕ ≈ 5 T into the REBCO film with little or no degradation of T c is an effective methodology for improving B irr at 77.3 K. In this study, to achieve a high B irr and J c , especially at a liquidnitrogen temperature of 77.3 K, we fabricated a SmBCO film with a high T c (91.1 K), including well-aligned BHO nanorods with the appropriate B ϕ ≈ 5.8 T.…”
mentioning
confidence: 99%
“…Awaji et al reported that wellaligned nanorods play an important role in achieving the high performance of the B irr . 13) Horii et al reported that B irr at T=T c = 0.9 increased with B ϕ up to ∼5 T and became saturated (or decreased) for B ϕ > 5 T. 14) Therefore, we expect that the introduction of well-aligned nanorods with B ϕ ≈ 5 T into the REBCO film with little or no degradation of T c is an effective methodology for improving B irr at 77.3 K. In this study, to achieve a high B irr and J c , especially at a liquidnitrogen temperature of 77.3 K, we fabricated a SmBCO film with a high T c (91.1 K), including well-aligned BHO nanorods with the appropriate B ϕ ≈ 5.8 T.…”
mentioning
confidence: 99%